International Taxation in the Digital Era: Toward Fair and Sustainable Regulatory Frameworks - Setyorini, Noni; Lestari, Dwirani Fauzi (Indonesian Scientific Publication, 2024)
The rapid growth of the digital economy has transformed global commerce and presented significant challenges for international taxation. This study provides a narrative review of cross-border taxation issues and regulatory responses, with a focus on identifying challenges, evaluating national approaches, and assessing multilateral frameworks. Literature was systematically collected from leading academic databases, including Scopus, Web of Science, and Google Scholar, using keywords such as digital economy, cross-border taxation, and regulatory responses. Inclusion criteria emphasized studies addressing digital services taxes, tax compliance, and emerging technologies in fiscal systems. Results reveal four dominant themes: cross-border taxation challenges, national regulatory responses, multilateral initiatives, and the implications of emerging technologies. Evidence shows that the lack of physical presence undermines tax enforcement, national approaches vary in effectiveness, and OECD’s BEPS framework, while promising, faces political and technical obstacles. Moreover, digital assets such as cryptocurrencies and NFTs complicate valuation and jurisdiction, demanding new regulatory strategies. The discussion highlights how systemic inequities disadvantage developing economies, while advanced economies benefit from stronger institutions. Solutions proposed in the literature include multilateral cooperation, blockchain-based transparency tools, and context-specific digital services taxes. The review concludes by stressing the urgency of inclusive global reforms, investments in administrative capacity, and further empirical research to ensure fair, effective, and sustainable digital taxation. These findings provide critical insights for policymakers and researchers seeking to align fiscal systems with the realities of the digital economy.